2018
DOI: 10.7567/jjap.57.11uf16
|View full text |Cite
|
Sign up to set email alerts
|

Domain orientation relationship of orthorhombic and coexisting monoclinic phases of YO1.5-doped HfO2 epitaxial thin films

Abstract: Domain structures with ferroelectric and ferroelastic characteristics of the epitaxial thin films of the polar orthorhombic phase of 7 mol % YO 1.5doped HfO 2 (YHO) were investigated by aberration-corrected scanning transmission electron microscopy (STEM). The high-angle annular darkfield (HAADF)-STEM images of the YHO thin film reveal that the individual domain size is approximately 10 nm. Multislice simulation demonstrated that STEM imaging can detect individual domains on the nanoscale avoiding superpositio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…This was experimentally observed by XRD in YHO films on YSZ(001) . Local analysis by transmission electron microscopy (TEM) revealed a lateral size of the crystallites of around 10 nm and that grain boundaries were along {100} or {110} planes . Shimizu et al observed that films on indium–tin oxide (ITO) buffered YSZ(001), presenting only b - and c -oriented domains ( c -axis was considered the polar axis), had large polarization of around 30 μC/cm 2 .…”
Section: Epitaxial Ferroelectric Doped Hfo2 Films On Yttria-stabilize...mentioning
confidence: 82%
See 1 more Smart Citation
“…This was experimentally observed by XRD in YHO films on YSZ(001) . Local analysis by transmission electron microscopy (TEM) revealed a lateral size of the crystallites of around 10 nm and that grain boundaries were along {100} or {110} planes . Shimizu et al observed that films on indium–tin oxide (ITO) buffered YSZ(001), presenting only b - and c -oriented domains ( c -axis was considered the polar axis), had large polarization of around 30 μC/cm 2 .…”
Section: Epitaxial Ferroelectric Doped Hfo2 Films On Yttria-stabilize...mentioning
confidence: 82%
“…34 Local analysis by transmission electron microscopy (TEM) revealed a lateral size of the crystallites of around 10 nm, and that grain boundaries were along {100} or {110} planes. 35 Shimizu et al 36 observed that films on indium-tin oxide (ITO) buffered YSZ(001), presenting only b-and c-oriented domains (c-axis was considered the polar axis), had large polarization of around 30 µC/cm 2 . This suggested that ferroelectric switching should imply ferroelastic domain switching, which was later confirmed experimentally by micro-diffraction, focusing a synchrotron radiation beam on poled and pristine capacitors (Figure 2) where vanishing of (0l0) reflections was observed after junction cycling indicating a polarization rotation from in-plane to out of plane.…”
Section: Epitaxial Ferroelectric Doped Hfo2 Films On Yttria-stabilize...mentioning
confidence: 99%
“…This was unexpected because domain walls with angles of 90° and 180° only were predicted and observed in previous studies of hafnia‐based compounds. [ 35,36 ] Figure 4i,j shows two types of coherent interfaces between o‐HZO and m‐HZO phases, and the coherent interface shown in Figure 4i is reported for the first time. Phase transformation between the m‐phase and o‐phase most likely occurs at this coherent interface, which could be important for exploring the origins of wake‐up and fatigue processes.…”
Section: Resultsmentioning
confidence: 98%
“…In contrast, at thicknesses below 20 nm, the film becomes thinner than the typical domain size. In such cases, domains are rarely stacked in the thickness direction. A previous PFM study on PZT films 400 nm thick indicated that the configurations of the domain walls near the grain boundary and far from the grain boundary are different, causing the difference in piezoelectric response nonlinearity, while such a mechanism is unlikely to occur in ultrathin films.…”
Section: Resultsmentioning
confidence: 99%